Presentation of retrofitting methodologies for automated manufacturing cells for the industry concept 4.0. - Rosário, João Mauricio; Hermini, Helder Aníbal; Bianchi, Fernando (Revista Gestão da Produção Operações e Sistemas, 2020)
This paper proposes the retrofitting of equipment and processes available in a manufacturing didactic plant, composed of workstations embedded in its automated systems, formed by actuators and sensors connected to the AS-i network and at the PLC of each station, which are connected in PROFIBUS industrial network, concepts of Industry 3.0. The objective is to update it to work applying the concepts of Industry 4.0, emphasizing the integration of information through networks of Industrial Automation and Internet. To achieve this objective integration of Automation Technology (TA) with Information Technology (IT) is necessary. Allowing the integrated educational exercise of the technologies found in the Automated Industrial Manufacturing Systems, such as communication networks, process control and production management, control and supervision of complete automated assembly processes that takes place on the platform is possible through a remote connection via internet (remote laboratory). Thus, teaching and research groups in multiple locations can share information quickly and develop such simultaneously groups in multiple locations can share information quickly and develop such simultaneously.